Comparative Study of Different Polar Groups of EPA‐Enriched Phospholipids on Ameliorating Memory Loss and Cognitive Deficiency in Aged SAMP8 Mice - Zhou, Miao‐miao; Che, Hong‐xia; Huang, Jia‐qi; Zhang, Tian‐tian; Xu, Jie; Xue, Chang‐hu; Wang, Yu‐ming (Molecular nutrition & food research, 2018)
Scope Recent studies have shown that omega‐3 PUFAs enriched phospholipids (n‐3 PUFA‐PLs) have beneficial effects on memory and cognition. However, most reports only attribute the benefit to docosahexaenoic acid (DHA) and pay little attention to eicosapentaenoic acid (EPA). Methods and results We investigate the effect of EPA‐enriched phospholipids on cognitive deficiency in senescence‐accelerated prone 8 (SAMP8) mouse. Ten‐month‐old SAMP8 mice are fed with 2% (w/w) EPA‐enriched phosphatidylcholine/phosphatidyl ethanolamine (EPA‐PC/PE; EPA:DHA = 46.8:3.01) or 2% EPA‐enriched phosphatidylserine (EPA‐PS; biosynthesized from EPA‐PC/PE) for 8 weeks; we then test the behavioral performances in the Barnes maze test and Morris maze test; the changes of oxidative stress, apoptosis, neurotrophic factors, tau phosphorylation, and Aβ pathology are also measured. The results of behavior tests indicate that both EPA‐PC/PE and EPA‐PS significantly improve memory and cognitive deficiency. It is found that remarkable amelioration of oxidative stress and apoptosis occurs in both EPA‐PC/PE and EPA‐PS groups. EPA‐PS shows more ameliorative effects than EPA‐PC/PE on neurotrophic activity by decreasing hyper‐phosphorylation of tau and depressing the generation and accumulation of β‐amyloid peptide (Aβ). Conclusion These data suggest that EPA‐PS exhibits better effects than EPA‐PC/PE on ameliorating memory and cognitive function, which might be attributed to the phospholipid polar groups. Dietary supplementation of EPA‐PC/PE and EPA‐PS can ameliorate cognitive deficiency in aged SAMP8 mice. Further investigation suggests that both EPA‐PC/PE and EPA‐PS can depress oxidative stress and alleviate the apoptosis in hippocampus. Moreover, EPA‐PS presents more notable benefits than EPA‐PC/PE on neurotrophic factors, tau pathology, and improving the generation and accumulation of Aβ.